Assessment of the Anterior Chamber Angle in Patients with Nanophthalmos: An Anterior Segment Optical Coherence Tomography Study. (May 2013) - Kara, Necip; Baz, Okkes; Altinkaynak, Hasan; Altan, Cigdem; Demirok, Ahmet
ABSTRACT Purpose: To quantitatively assess the parameters of anterior chamber and angle dimensions by anterior segment optical coherence tomography (AS-OCT) in nanophthalmos. Methods: In this prospective, cross-sectional and comparative study, 34 eyes of 34 healthy individuals (control group) and 37 eyes of 37 patients with nanophthalmos (study group) were enrolled. A single experienced ophthalmologist imaged and measured the right eye with the Visante AS-OCT. The anterior chamber angle (ACA), angle opening distance (AOD) at 500 and 750 µm from the scleral spur, and trabecular–iris space area (TISA) at 500 and 750 µm at the nasal and temporal angles were measured. Results: Mean nasal/temporal ACA was 44.90 ± 9.09/47.07 ± 8.69° in the control group and 32.15 ± 10.30/29.77 ± 10.57° in the study group (p < 0.001). Mean nasal/temporal AOD500 and AOD750 was 0.52 ± 0.18/0.53 ± 0.15 mm and 0.71 ± 0.26/0.71 ± 0.23 mm in the control group. The mean nasal/temporal AOD500 and AOD750 were 0.33 ± 0.12/0.31 ± 0.15 mm and 0.48 ± 0.16/0.47 ± 0.22 mm in the study group. Mean nasal/temporal TISA500 and TISA750 were 0.16 ± 0.06/0.17 ± 0.05 mm2 and 0.31 ± 0.11/0.33 ± 0.09 mm2 in the control group. Mean nasal/temporal TISA500 and TISA750 were 0.11 ± 0.04/0.09 ± 0.05 mm2 and 0.20 ± 0.07/0.20 ± 0.10 mm2 in the study group. All values were significantly lower in the study group compared with the control group. Conclusion: Determination of angle parameters using AS-OCT is a rapid noncontact method that is useful in patients with nanophthalmos. The findings demonstrated that nanophthalmic eyes had lower ACA parameters including ACA, AOD500, AOD750, TISA500 and TISA750 at the nasal and temporal angles.